BIOREMEDIATION STUDY: HYDROCARBON DEGRADING BACTERIA - Sutiknowati, Lies Indah (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
Many microorganisms capable of degrading petroleum components have been isolated and few of them seem to be important for petroleum biodegradation in natural environments. To identify the bacteria that play a major role in degradation of petroleum polynuclear aromatic hydrocarbons (PAHs), bacteria were enriched from seawater by using Naphthalene, Phenanthrene, Trichlorodibenzofuran and Benzo[a]pyrene as a carbon and energy source. The result of study that members of the genus Alcanivorax and Thalassospira became predominant in the enrichment cultures. The strains isolated in this study could grow on crude oil and degraded PAH components of crude oil. The number of cells increased to 8.1x106 cells g-1 after 14 days in subculture. PAH degradation proceeded parallel with the growth of bacteria cells. This observation which has been conducted in Marine Biotechnology Institute, Kamaishi, Iwate-ken, Japan suggests that Alcanivorax and Thalassospira play an important role in the degradation of petroleum PAHs in marine environment.